FRI0255 The 158vv fcgamma receptor 3a genotype is associated with response to rituximab in rheumatoid arthritis: results of an italian multicentre study. (23rd January 2014) - Quartuccio, L.; Fabris, M.; Pontarini, E.; Salvin, S.; Zabotti, A.; Benucci, M.; Manfredi, M.; Biasi, D.; Ravagnani, V.; Atzeni, F.; Sarzi Puttini, P.; Morassi, P.; et al.
Abstract : Background: Receptors for IgG allow antibody-dependent cell cytotoxicity, and the polymorphism 158V/F (rs396991) of the Fc fragment of IgG type 3A (FCG3A) was investigated as a genetic factor influencing disease response after rituximab (RTX) therapy in haematologic and rheumatic diseases. Objectives: The aim of this study was to better evaluate of the association between 158V/F FCGR3A polymorphism and response to RTX, by analysing a larger series of patients and by dissecting the results at month +4 and at month +6 after treatment. The pharmacogenetic data were also integrated with established clinical predictors of response to RTX in RA, i.e., rheumatoid factor (RF) and/or anti-cyclic citrullinated peptides (anti-CCP) antibodies, baseline DAS28, baseline HAQ, number of TNF blockers previously failed. Methods: The study analysed 212 RA patients. Patients were referred to 13 different rheumatologic Centres in Italy. They were unselected and represented the majority of the RA subjects treated with RTX in any single participating centre. Patients were followed for at least 6 months after RTX treatment, from 2004 to 2011, and data were collected after the first cycle of RTX. EULAR response was evaluated at months +4 and +6 after the first RTX infusion. The FCGR3A polymorphism was analysed by PCR followed by Sanger sequencing. Results: The FCGR3A genotypes were associated with EULAR response (good or moderate) at month +6 [response in 34/38 (89.5%) VV vs. 70/106 (66%) VF and in 51/77 (66.2%) FF patients; p=0.01], but not at month +4 [response in 32/37 (86.5%) VV vs. 69/102 (67.6%) VF and 53/73 (72.6%) FF patients; p=0.09]. Loss of response was observed only in VF and FF carriers [(VV vs VF vs FF: 0/37 (0%) vs 11/102 (10.8%) vs 12/73 (16.4%); p=0.02)]. Probability of response at month +6 was very high when at least two of the three following items selected by multivariate analysis were present: positive rheumatoid factor and/or anti-CCP antibodies, previous treatment with ≤1 anti-TNF agent, and 158VV FCGR3A genotype (p<0.0001; OR 7.9, 95%CI 4.1-15.1). Conclusions: The 158VV FCGR3A genotype was associated with response to RTX in a large cohort of RA patients. Previous results from a similar French study (1 ) were partially confirmed in an Italian population. Patient genotyping may be helpful to plan RTX treatment, and, notably, may be integrated with clinical predictors. References: Ruyssen-Witrand A, et al. FcY receptor type IIIA polymorphism influences treatment outcomes in patients with rheumatoid arthritis treated with rituximab. Ann Rheum Dis. 2012;71:875-7 Disclosure of Interest : None Declared